No effect of donepezil on striatal dopamine release in mild to moderate Alzheimer's disease. Issue 1 (17th December 2009) - Reeves, S; Brown, R; Matthews, D; Howard, R; Grasby, P
Abstract : Objective: Work in experimental animals suggests that an interaction with dopaminergic networks might explain some of the therapeutic effects of the cholinesterase inhibitor class of drugs. This study aimed to test whether acute (single 5 mg) or 4–8 weeks (5–10 mg) of treatment with oral donepezil would elicit measurable striatal dopamine (DA) release in patients with mild to moderate Alzheimer's disease. A second aim was to establish whether any increase in DA levels would be associated with improvements in cognitive and motor function. Methods: Percentage change in [ 11 C]-raclopride (RAC) binding potential (BPND ) between baseline and treatment conditions was used to provide a measure of DA release. Repeated measures ANOVA was used to determine the effect of treatment on [ 11 C]-RAC BPND and neuropsychological test performance. Results: Contrary to our prediction there was no significant change in [ 11 C]- RAC BPND after acute or a mean of 6 weeks (range 4–12) of treatment with donepezil. Although motor speed (finger tapping) improved following 4–12 weeks of treatment with donepezil (F1, 19  = 8.7, p = 0.009), this was not associated with the degree of change in [ 11 C]-RAC BPND . Conclusions: Our findings provide no evidence that striatal DA levels are altered during the first 3 months of donepezil treatment. However, we cannot rule out the possibility that extrastriatal effects may be occurring.